Radioactivity levels of 238U and 232Th, the α and β activities and associated dose rates from surface soil in Ulu Tiram, Malaysia - Abdul Rahman, A.T (Akadémiai Kiadó, co-published with Springer Science+Business Media B.V., Formerly Kluwer Academic Publishers B.V., 2007)
A survey was carried out to determine terrestrial gammaradiation dose rates, the concentration level of 238U and 232Th and α and β activities for the surface soil in Ulu Tiram, Malaysia A 125 measurements were performed using a NaI(T1) gamma-ray detector with crystal size of 1″ × 1″ on 15 soil samples collected from the site area about 102 km2238U and 232Th concentrations were determined in soils by using hyper pure germanium (HPGe) gamma-ray spectrometry. The activity of α and β from the surface soil was counted by using alpha beta counting system. The average value of 238U and 232Th concentrations in soil samples collected are 3.63±0.39 ppm within the range of 1.74±0.20 to 4.58±0.48 and 43.00±2.31 ppm within the range of 10.68±0.76 to 82 10±4.01 ppm, respectively. The average estimate of α and β activity in soil samples collected are 0.65±0.09 Bqg-1 and 0.68±0.08 Bqg-1, respectively. The average of terrestrial gamma-radiation dose rates measured in Ulu Tiram was found to be 200 nGy h -1, within the range of 96 to 409 nGy h-1. The population weighted outdoor annual effective dose was 1.2 mSv.